Turnitin Services in Plagiarism Prevention at The Rumah Ilmu UNNES - Fachriz, Retma Inayati; Purnomo, Sucipto Hadi; Cahyaningtyas, Annisa Dwi (Jurnal Penelitian Pendidikan, 2023)
Plagiarism is an academic crime that greatly disrupts the performance of a University. The creative works of writing created by the academic community of Semarang State University need to be protected for their authenticity. Sometimes students' writings in the process of creating written works in the form of theses, dissertations and dissertations must include other written works as citations to support the novelty of their writing. Since 2021, the Semarang State University Library Unit has been appointed as the gateway for selecting student writings to be submitted to the Final Assignment Examination. Through the procedures that have been prepared, each student who will take the final exam submits online in the form of a document file that will be processed by the Library Unit staff and provide the results of the document. From the documents that have been sent and uploaded in the Turnitin application, a similarity presentation is produced. The results of this similarity make it an interesting material to study the percentage level of the initial writing and the improvements sent in the similarity submission. This study will look at Turnitin data submitted in 2022. The data is 8000 Turnitin submission data and its improvements. From this data, it can be expected that this study aims to determine how effective the use of the Turnitin application is in filtering final assignment writing from students before being tested by the examining committee at the Faculty. After being tested and declared passed, this final assignment will be published in the Unnes repository on the page http://lib.unnes.ac.id . The output produced in this study is targeted to be published in a national journal indexed by Sinta, namely the Journal of Educational Research https://journal.unnes.ac.id/nju/index.php/JPP . This study is expected to be used as a reference for managers of library materials from students' work that are ready to be published so that they are safe from plagiarism.